Корпоративні права та обов’язки за законодавством України та Європейського Союзу - Марущак, Ярослав Сергійович; Марущак, Ярослав Сергеевич; Maruschak, Yaroslav S. (My University, 2018)
Дисертація на здобуття наукового ступеня кандидата юридичних наук заспеціальністю 12.00.03 - цивільне право і цивільний процес; сімейне право; міжнародне приватне право. - Національний університет «Одеська юридична академія», Одеса, 2018. Дисертація є першим у вітчизняній юридичній науці цивільно-правовим дослідженням правового регулювання корпоративних прав та обов’язків в Україні та ЄС. У дисертації охарактеризовано корпоративні права та обов’язки за законодавством України. Досліджено історичний розвиток корпоративних прав та обов’язків як у загальному контексті, так і на теренах сучасної України в рамках права Київської Русі, Австро-Угорської та Російської імперій, СРСР. Виявлено особливості створення та функціонування юридичних осіб корпоративного типу в Україні. Розглянуто корпоративні права та обов’язки як зміст корпоративних правовідносин. Досліджено загальні засади права компаній ЄС, національні та наднаціональні форми корпорацій в ЄС, виявлено особливості корпоративних прав та обов’язків їх учасників. Окреслено перспективи розвитку правового регулювання корпоративних прав та обов’язків на сучасному етапі європейської інтеграції України. Охарактеризовано процес адаптації вітчизняного корпоративного законодавства до норм права компаній ЄС. Виявлено проблеми на шляху до узгодження корпоративного законодавства України з правом компаній ЄС. Сформульовано науково обґрунтовані пропозиції з удосконалення чинного законодавства України щодо правового регулювання корпоративних прав та обов’язків.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.03 - гражданское право и гражданский процесс; семейное право; международное частное право. - Национальный университет «Одесская юридическая академия», Одесса, 2018. Диссертация является первым в отечественной юридической науке гражданско-правовым исследованием правового регулирования корпоративных прав и обязанностей в Украине и ЕС. В диссертации охарактеризованы корпоративные права и обязанности по законодательству Украины. Исследовано историческое развитие корпоративных прав и обязанностей как в общем контексте, так и на территории современной Украины в рамках права Киевской Руси, Австро Венгерской и Российской империй, СССР. Выявлены особенности создания и функционирования юридических лиц корпоративного типа в Украине. Рассмотрены корпоративные права и обязанности как содержание корпоративных отношений. Исследованы общие принципы права компаний ЕС, национальные и наднациональные формы корпораций в ЕС, выявлены особенности корпоративных прав и обязанностей их участников. Определены перспективы развития правового регулирования корпоративных прав и обязанностей на современном этапе европейской интеграции Украины. Охарактеризован процесс адаптации отечественного корпоративного законодательства к нормам права компаний ЕС. Выявлены проблемы на пути к согласованию корпоративного законодательства Украины с правом компаний ЕС. Сформулированы научно обоснованные предложения по совершенствованию действующего законодательства Украины относительно правового регулирования корпоративных прав и обязанностей.

Thesis for a Candidate Degree in Law, specialty 12.00.03 - Civil Law and Civil Procedure; family law; international private law. - National University “Odessa Law Academy”, Odessa, 2018. The dissertation is a complex study of legal regulation of corporate rights and obligations under the legislation of Ukraine and the law of the European Union. The dissertation describes corporate rights and responsibilities under the legislation of Ukraine. The historical development of corporate rights and responsibilities in the general context and in the areas of modern Ukraine within the framework of the right of Kyiv Rus, Austro-Hungarian and Russian Empires, the USSR has been researched. The features of creation and functioning of corporate entities in Ukraine are revealed. By analyzing the provisions of the current legislation, the legal doctrine, as well as taking into account the foreign understanding of the essence of the corporation and the established practice of using this term, the position on the recognition of the possibility of creating corporate entities in Ukraine in the following organizational and legal forms was further developed: economic partnerships (joint-stock companies , limited liability companies, partnerships with partners, full and limited partnerships) and production cooperatives, private enterprises and farm enterprises operating on the basis of private ownership of several persons, enterprises of consumer co-operation, formed by several consumer societies. Corporate rights and obligations considered as a content of corporate relations. Author’s definition of corporate legal relations is formulated as regulated by the rules of the law of internal relations, which are formed between a corporate entity and its participants, as well as between the participants (founders) of such a legal entity in connection with the creation, management and termination of the activity of such a legal entity, the implementation of corporate rights and obligations of the participants, as well as other relations involving the legal entity of a corporate law or its participant, aimed at the implementation of corporate rights. The general principles of the EU company law, national and supranational forms of corporations in the EU are investigated, features of corporate rights and obligations of their participants are revealed. The corporate rights and obligations of corporate-type legal entities created in the EU Member States are the subject of harmonization of EU law in the field of company law only to the extent that it is necessary to ensure an equivalent level of protection of their interests within the Community, the creation of an enabling environment for the conclusion of crossborder transactions and the effective functioning of the internal market. The prospects of development of legal regulation of corporate rights and obligations at the present stage of European integration of Ukraine are outlined. The process of adaptation of domestic corporate legislation to the norms of the EU company law is described. Problems are found on the way to the harmonization of Ukrainian corporate legislation with the right of EU companies. Taking into account the established principles of legal regulation of corporate rights and obligations under EU law, in the first place, processes of harmonization of domestic corporate legislation more closely affect the joint-stock company form (mostly public jointstock companies) and in the smaller one - limited liability companies. The scientifically grounded proposals on improvement of the current legislation of Ukraine concerning the legal regulation of corporate rights and responsibilities are formulated.
дис. ... канд. юрид. наук: 12.00.03
Марущак Я.С. Корпоративні права та обов’язки за законодавством України та Європейського Союзу: дис. ... канд. юрид. наук: 12.00.03 / Марущак Ярослав Сергійович. - Одеса, 2018. - 214 с
Keywords: корпоративне право; корпоративне законодавство; корпоративні права; корпоративні обов’язки; право компаній ЄС; корпорації; європейська інтеграція України; корпоративное право; корпоративное законодательство; корпоративные права; корпоративные обязанности; право компаний ЕС; корпорации; европейская интеграция Украины; corporate law; corporate law; corporate legislation; corporate rights; corporate responsibilities; EU company law; corporations; European integration of Ukraine